MENGATASI KECEMASAN MENGHADAPI MENSTRUASI REMAJA AWAL MELALUI PENDEKATAN RATIONAL EMOTIVE BEHAVIOR THERAPY - Diyah Utari Lina Novita Sari; Masturi Masturi; Edris Zamroni (Universitas Muria Kudus, 2022)
REBT is a step in improving and changing irrational attitudes, perceptions, ways of thinking, beliefs and views of clients into rational ones. The purpose of this study is to describe counseling through a rational emotive behavior therapy approach to overcome anxiety when facing menstruation in early adolescence through seventh grade students of SMP Negeri 4 Kudus.This research method is descriptive qualitative. The dependent variable in this study is anxiety during menstruation, while the independent variable is guidance services with discussion techniques. Data collection techniques in the form of observation, documentation, interviews. Analysis with data review methods, data reduction, data coding and data analysis.The results of the study were counseling on the REBT approach through discussion techniques with steps such as: assessment, antecedent event/activity, believe, consequence, disputing/treatment, effect/expectation and closure, and factors that cause anxiety during menstruation include lack of knowledge about menstruation, already entering menstruation. age of menarche, lack of support and love for mothers and lack of sources of information about menstruation.